Anaerobic endodontic microflora in dynamics of chronic apical periodontitis treatment - V. L. Kukushkin; A. A. Dutova; E. A. Kukushkina; M. Yu. Kordyuk; M. V. Smirnitskaya (Эндодонтия Today)
26 patients with chronic apical periodontitis had clinical and laboratory examinations with a following treatment. The anaerobic microflora of 40 dental root canals were examined before and after a week treatment to assess the efficacy of the antiseptic paste «Metapex». The sampling and PCR study of the root canal contents indicate the insufficient efficacy of a single paste application. Thus, metronidazole-containing compositions effectively suppressing the anaerobic microflora of root canals are more preferable in a dental practice.